Glial Extracellular Vesicles Production And Lipid-Dependent Neuroprotection: A New Case Study - Benzi Juncos, Oriana Nicole (2025)
The dithiocarbamate pesticide maneb has been associated with parkinsonism after chronic exposure. We have previously demonstrated that astrocytes’ secretome triggers protective signals associated with resolution pathways in neuronal cells exposed to maneb. In the present study, we aimed to characterize the secretome of primary glial cells, specifically their extracellular vesicle (EV) population and its role in neuroprotection. EVs are membranous nanostructures secreted under both normal and pathological conditions, thus playing a crucial role in neuron-glia communication. Firstly, we isolated glial cells from mice brains and obtained mixed glial cultures (MGC) and purified microglia and astrocytes, which were characterized by assessing activation markers using RT-qPCR. Microglia showed increased mRNA expression of Tnf-α, with no changes in Il-1β or Il-6, and increased Il-10 and Tgf-β, along with higher Arg- 1 levels, consistent with a M2 phenotype. In contrast, astrocytes displayed increased Tgf-β but no changes in the A1 marker C3 or other cytokines. Conversely, MGC exhibited a decreased expression of Arg-1 and C3, alongside higher expression of Il1-β and the A2 marker Emp1, demonstrating differential responses in mixed and isolated cultures. To study EVs derived from the different glial cultures challenged with maneb, size-exclusion chromatography was used for their isolation from the secretome. Through micro-flow cytometry, we found that maneb- exposed astrocytes and microglia, but not MGC, secreted nearly fivefold more EVs than controls, with no change in total EV protein content. Characterization by nanoparticle tracking analysis revealed a broader size distribution with bigger EVs compared to controls for the isolated cultures, coinciding with increased levels of total phospholipids (PL). In addition, GC- MS analysis of fatty acids from PL displayed a differential contribution of the polyunsaturated fatty acids 22:6 and 20:4 in EVs derived from maneb-exposed astrocytes. Moreover, live imaging revealed a significant reduction of EV uptake in neurons under pesticide exposure. Interestingly, pesticide-induced mitochondrial alterations in neurons were attenuated by EVs derived from maneb-exposed astrocytes with no changes in cell viability. This contrasted with the neuroprotective role of the astrocytes’ secretome, which was associated with resolution mechanisms depending on FPR2/ALX activation mediated by lipoxin A4, a pro-resolving lipid mediator derived from 20:4. Our results suggest that astrocytes adapt their EV formation and composition in response to pesticide-induced toxicity, a mechanism that may play a pivotal role in mediating astrocytic neuroprotection and that can synergize with pro-resolving factors of a lipid nature.